Noncoding RNAs in Cardiac Autophagy following Myocardial Infarction. (3rd June 2019) - Turkieh, Annie; Charrier, Henri; Dubois-Deruy, Emilie; Porouchani, Sina; Bouvet, Marion; Pinet, Florence
Abstract : Macroautophagy is an evolutionarily conserved process of the lysosome-dependent degradation of damaged proteins and organelles and plays an important role in cellular homeostasis. Macroautophagy is upregulated after myocardial infarction (MI) and seems to be detrimental during reperfusion and protective during left ventricle remodeling. Identifying new regulators of cardiac autophagy may help to maintain the activity of this process and protect the heart from MI effects. Recently, it was shown that noncoding RNAs (microRNAs and long noncoding RNAs) are involved in autophagy regulation in different cell types including cardiac cells. In this review, we summarized the role of macroautophagy in the heart following MI and we focused on the noncoding RNAs and their targeted genes reported to regulate autophagy in the heart under these pathological conditions.